Role of Sintering, Co-particles on Properties of Milled Al-Zn-Mg-Cu Matrix Produced via PM - Haider T. Naeem (Journal of Global Pharma Technology, 2018)
In the current study, mechanically alloying has done to synthesizing Aluminum-Zinc-Magnesium-Copper-Cobalt powders via high-energy ball milling. The green compacts milled Al-Zn-Mg-Cu-Co powders were compacting using hydraulic press uniaxial at 300 MP a. The milled mixtures Al-compacts were conducted by the sintering treatments at various temperatures of 400-600 °C for 1-1.5 hours. Over all ball-milling route turn on: a ratio weight of ball-to-powder about 10:1, the speed of rotation 350 rpm; and the milling time of 8 hours. The assessment of the precipitates particles and intercom pounds of the milled Al-matrixes PM undergone conditions of sintering process were examined using the X-ray diffraction (XRD) and scanning 'electron microscopy-(SEM) with energy-dispersive X-ray spectroscopy (EDS).Outcomes of micro structural the sintered Al-PM alloys investigated having a precipitations and cobalt-compounds in the matrix during several treatments. The highest Vickers hardness recorded of Al-Zn-Mg-Cu-Co PM alloy under sintering at 600 °C.Keywords: Aluminium-Cobalt Alloys; Sintering; Hardness.